PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA PADA MATERI PENGOLAHAN DATA SISWA SEKOLAH DASAR KELAS IV - Shollaa, Abdaa Idzaa; Fatkhur Rohman; Dani Syahpitri Ginting; Nurhanurawati; Fadila Hanum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to design Student Worksheets (LKPD) based on Discovery Learning in Mathematics lessons on Data Processing for fourth grade elementary school students. The development of this LKPD is based on the need for learning tools that can encourage active student involvement and improve understanding of mathematical concepts, especially in data processing which is often considered difficult for students to understand. This study uses the Research and Development (R&D) method with a development model that adapts the initial research steps, prototype phase, and assessment phase according to the Plomp model. Validation was carried out by material, media, and language experts to ensure that the content, appearance, and language of the LKPD were suitable for use. The results of the validation process showed that the developed LKPD met the validity and practicality criteria, with a validity score of and practicality reaching %, which is classified as very practical. Limited trials involving teachers and fourth grade students showed that LKPD based on Discovery Learning was effective to use, making it easier for students to understand concepts independently, and increasing their active participation and understanding of data processing materials. Thus, this LKPD can be an innovative alternative in the process of meaningful mathematics learning at the elementary school level.